KEABSAHAN PEMBUKTIAN AKTA NOTARIS DI PENGADILAN SEBAGAI AKTA OTENTIK (Kajian Putusan No. 3591K/PDT/2018 ) - Hazar Kusmayanti; Yuda Anrova (Departemen Hukum Perdata, 2020)
The evidentiary process requires evidence which is regulated under the civil procedure law in Article 164 HIR. Supreme Court decision number 3591K/Pdt/2018, discusses documentary evidence in the form of an agreement to transfer and transfer land rights. Mahakamah Agung’s decision number 3591K/Pdt/2018 states that the deed has no legal force because the land object of the dispute has been issued a legally valid right to build (HGB) certifi cate. The purpose of this paper is to fi nd out the legal considerations of the decision of the Supreme Court of the Republic of Indonesia regarding the validity related to positive law in Indonesia. The research method used is a normative juridical approach with research specifi cations in the form of descriptive analytical through secondary data obtained from literature studies. The data analysis method used is qualitative normative method. The conclusion was obtained that the deed of agreement of transfer and transfer of land rights as outlined in deed number 255 is legally valid because the agreement was made by fulfi lling the validity requirements of the agreement in Article 1320 of the Civil Code, however the judge did not provide further explanation in the judge’s consideration regarding the validity of the letter.